2017
DOI: 10.1121/1.4976037
|View full text |Cite
|
Sign up to set email alerts
|

Effects of linguistic experience on the perception of high-variability non-native tones

Abstract: Whether tone language experience facilitates non-native tone perception is an area of research that previously yielded conflicting results, potentially because of the lack of systematical control of speaker normalization effects across studies. Under a high-variability testing condition with controlled speaker normalization cues, Cantonese (native controls), Mandarin (Cantonese-naive tone listeners), and English (non-tone listeners) listeners identified three Cantonese level tones. The results indicate a facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 16 publications
2
27
0
Order By: Relevance
“…Previous tone training studies found that stimulus variability of syllables and speaker would modulate the perceptual learning outcome [48,[65][66][67][68]. Thus, a future direction of this line of research is to investigate whether a greater or a smaller acoustic variability (of syllables and/or speakers) of training stimuli would modulate the size of the overnight consolidation effect in facilitating the abstraction of novel phonetic information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous tone training studies found that stimulus variability of syllables and speaker would modulate the perceptual learning outcome [48,[65][66][67][68]. Thus, a future direction of this line of research is to investigate whether a greater or a smaller acoustic variability (of syllables and/or speakers) of training stimuli would modulate the size of the overnight consolidation effect in facilitating the abstraction of novel phonetic information.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Mandarin listeners are more sensitive to pitch contour than pitch height [44][45][46][47]. Specifically, Mandarin listeners had a great difficulty distinguishing (e.g., Cantonese) level-level tonal contrasts [35,[48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…Research on how L1 experience shapes the perception of non-native prosody, however, is inconclusive. Other studies support the claim that linguistic experience with a broad prosodic category does, in fact, facilitate perception of nonnative prosodic categories, e.g., [9,10]. One source of evidence for this claim comes from [10] in which native Mandarin listeners outperformed native English listeners in a Cantonese tone identification task with speaker normalization cues controlled.…”
Section: Introductionmentioning
confidence: 78%
“…On the other hand, our approach clearly affected the overall rater accuracy, (cf. Chang, Yao, & Huang, ) and contributed to only moderate agreement among raters. We recognize that if raters were given more exemplars from each participant, and thus had become more familiar with the acoustics of each speaker's voice, we may have found a different pattern of results.…”
Section: Discussionmentioning
confidence: 99%